Hypothesis: increase of the ratio singlet oxygen plus superoxide radical to hydrogen peroxide changes stress defense response to programmed leaf death - Sabater, Bartolome; Martín, Mercedes (Frontiers in Plant Science, 2013)
The level of reactive oxygen species (ROS) increases under different stresses and, by destroying cellular components, may cause cell death. In addition, ROS are part of the complex network of transduction signals that induce defence reactions against stress or, alternatively, trigger programed cell death (PCD), and key questions are the levels of each ROS that respectively determine defence and death responses of the cell. The answer to those questions is difficult because there are several patterns of cell death that frequently appear mixed and are hardly distinguishable. Moreover, although considerable progresses have been achieved in the determination of the levels of specific ROS, critical questions remain on the ROS level in specific cell compartments. By considering chloroplasts as the main source of ROS in photosynthetic tissues at light, a comparison of the levels in stress and senescence of the chloroplastic activities involved in the generation and scavenging of ROS suggests plausible differences in the levels of specific ROS between stress defence and death. In effect, the three activities of the chlororespiratory chain increase similarly in stress defence response. However, in senescence, superoxide dismutase (SOD), that converts superoxide anion radical (O2•–) to hydrogen peroxide (H2O2,) decreases, while the thylakoid Ndh complex, that favours the generation of singlet oxygen (1O2) and O2•–, and peroxidase (PX), that consumes H2O2, increase. The obvious inference is that, in respect to defence response, the ratio (1O2 plus O2•–)/H2O2 is increased in the senescence previous to cell death. We hypothesize that the different ROS ratios, probably through changes in the jasmonic acid/ H2O2 ratio, could determine the activation of the defence network or the death network response of the cell.